AB0284 Long term safety of iv golimumab and comparisons with sc golimumab in rheumatologic conditions: results from the 120-day safety report of go-further trial. (23rd January 2014) - Westhovens, R.; Bingham, C. O.; Weinblatt, M.; Fleischmann, R.; Keystone, E.; Hsia, E. C.; Hsu, B.; Kim, L.; Mudivarthy, S.; Mack, M.; Goldstein, N.; Braun, J.; et al.
Abstract : Objectives: To describe safety of IV GLM in RA from the Ph3 GLM IV program. AE rates of interest are indirectly compared to those observed in the GLM SC clinical program across rheumatologic indications. Methods: 2 multicenter, randomized, double-blind, PBO-controlled studies were included in the integrated IV safety analysis. GO-LIVE evaluated IV PBO or GLM 2mg/kg or 4mg/kg, ± MTX q12wks in pts with active RA despite MTX. GO-FURTHER is evaluating GLM 2mg/kg IV at wks 0, 4, and q8wks +MTX in active RA despite MTX. In the SC GLM program (GO-FORWARD, GO-BEFORE, GO-AFTER [RA], GO-REVEAL [PsA], GO-RAISE [AS]), PBO or GLM (50mg/100mg) was administered SC q4wks in Ph3 and q2 or 4 wks in Ph2. Approx. half of pts received MTX. Safety findings for the Ph3 GLM IV RA studies combined through the IV dosing period of GO-LIVE (median 60wks exposure) and through the August 15, 2012 cut-off for GO-FURTHER (median 92wks exposure) are reported; for the ongoing SC studies the data cut was through wk160. Comparison of targeted safety events between IV and SC GLM are reported. Pts who received ≥1administration were analyzed. Results: 1210pts were treated with IV GLM in the integrated Ph3 RA IV studies with median duration of follow-up of 72.7wks. Overall AEs observed in the integrated Ph3 RA IV program are summarized (Table ). Since follow-up was longer for the SC rheumatology program, more overall events were observed;however when corrected for events/100 pt yrs, no difference in AE rates or significant SAEs were observed between GLM IV and SC. Incidence of non-serious infusion reactions (median 30 min infusions) remained low regardless of infusion length, and no serious infusion reactions, requiring study d/c, were reported. NMSC(incidence/100 pt-yrs of f/u:0.49[95%CI:0.33, 0.71] vs 0.14[95%CI:0.03, 0.42] for GLM SC vs GLM IV) and lymphoma rates were numerically higher in the GLMSC grp vs the GLMIV grp. Image/graph: Conclusions: Overall safety of IV GLM in RA pts observed through Aug 15, 2012 continue to demonstrate an acceptable safety profile. Rates for events of interest such as malignancies and serious infections in the IV studies are comparable with or lower than rates in the SC studies in RA pts, AS, and PsA. Follow-up through 2yrs will provide information regarding long-term safety of IV GLM. Disclosure of Interest: R. Westhovens Grant/research support from: Janssen R&D, LLC, C. Bingham III Grant/research support from: Janssen R&D, LLC, M. Weinblatt Grant/research support from: Janssen R&D, LLC, R. Fleischmann Grant/research support from: Janssen R&D, LLC, E. Keystone Grant/research support from: Janssen R&D, LLC, E. Hsia Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, B. Hsu Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, L. Kim Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, S. Mudivarthy Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, M. Mack Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, N. Goldstein Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, J. Braun Grant/research support from: Janssen R&D, LLC, A. Kavanaugh Grant/research support from: Janssen R&D, LLC, A. Mendelsohn: None Declared, J. Kay: None Declared